Advances in Biochemical Engineering
DOI: 10.1007/bfb0048091
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of hydrogen

Abstract: In developing heterotrophic microbial processes for producing hydrogen, greater emphasis must be placed on systems which not only generate protons and electrons, l~ut also on the capability of shunting electrons toward H 2 production rather than toward alternative reductive activities. Likewise, systems must be sought which actively carry out a reductive cleavage of water with active release of hydrogen. Photosynthetic systems need development study and more research is required for study of hydrogen productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 416 publications
(386 reference statements)
1
31
1
Order By: Relevance
“…McCarty and Mosey (1991) proposed that butyrate-fermentative Clostridia are obligate hydrogen-producing bacteria that have retained the ability to produce butyrate as a response to low pH values, and this type of fermentation competes with the non-hydrogen-producing propionate fermentation pathway. These assumptions are consistent with other reports by many investigators that butyrate-acetate fermentation is the main metabolic pathway for anaerobic hydrogen-producing bacteria (Chen et al, , 2002Fang and Liu, 2002;Mizuno et al, 2000;Noike and Mizuno, 2000;Payot et al, 1998;Zajic et al, 1978).…”
Section: Implication Of Fermentative Routes For Hydrogen Productionsupporting
confidence: 93%
See 1 more Smart Citation
“…McCarty and Mosey (1991) proposed that butyrate-fermentative Clostridia are obligate hydrogen-producing bacteria that have retained the ability to produce butyrate as a response to low pH values, and this type of fermentation competes with the non-hydrogen-producing propionate fermentation pathway. These assumptions are consistent with other reports by many investigators that butyrate-acetate fermentation is the main metabolic pathway for anaerobic hydrogen-producing bacteria (Chen et al, , 2002Fang and Liu, 2002;Mizuno et al, 2000;Noike and Mizuno, 2000;Payot et al, 1998;Zajic et al, 1978).…”
Section: Implication Of Fermentative Routes For Hydrogen Productionsupporting
confidence: 93%
“…Escherichia coli, Enterobacter aerogenes, Clostridium butyricum, Clostridium acetobutyricum, and Clostridium perfringens have been found to produce hydrogen under anaerobic conditions (Jungermann et al, 1973;Karube et al, 1982;Kim et al, 1984;Kumar and Das, 2000;Thauer et al, 1972Thauer et al, , B 1977. Clostridium species are important anaerobic hydrogen-producing microorganisms used for studying the conversion of carbohydrate to hydrogen gas (Nandi and Sengupta, 1998;Reimann et al, 1996;Zajic et al, 1978). Clostridium species are Gram-positive rods that form spores.…”
mentioning
confidence: 99%
“…These are not necessarily the only hydrogen producers in the sea. Hydrogen production is common among fermentative bacteria (Zajic et al 1978), so there could be many other marine facultatively anaerobic bacteria that can produce hydrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Scranton (1983Scranton ( , 1984 has demonstrated that hydrogen is released from marine cyanobacterial aggregates and several other microorganisms are known to produce hydrogen (Zajic et al 1978). Biological hydrogen consumption also appears to be important in the marine hydrogen cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Cellulose degradation was not affected. High H, concentrations are known to inhibit H, production by some anaerobes (Zajic et al, 1978). Our observations during cultivation (500 ml flasks) in cellobiose medium (with growth pH controlled) indicated that about 15 % H, accumulated in the gas phase after 24 h incubation if the head space was not flushed with N,/CO, (80 :20, v/v) every 12 h. Although the growth (A660 1.0) and cumulative H, produced [ 5 mmol (100 ml medium)-'] after 24 h incubation were similar to those for cultures in which the head space was flushed every 12 h, the cumulative H, production after 36 h incubation (6.38 mmol) was 15 % lower than that for cultures in which the head space was flushed.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%